Sistema de control y monitoreo para una planta de tratamiento de agua a escala (2018)
Steel is a material widely used nowdays, however, it has as limitation that it corrodes itself when it is exposed. For this reason, it has to be chemically treated to protect it from the corrosion. This chemical process generates wastewater which is highly polluting, and according to this argument, it was proposed to develop a low-cost wastewater treatment plant prototype that can work in appropriates industrial environments. Since it has to be low-cost, it was decided to work with Arduino as part of the technological solution. For the development of this project, different methods for the treatment of wastewater were analyzed, looking for different ways to automate the process and to make it more effective. The project also proposes to implement a web service for the monitoring stage, which will allow users to follow up the process in real time through mobile